Perineuronal nets and GABAergic cells in the inferior colliculus of guinea pigs - Foster, Nichole L.; Mellott, Jeffrey G.; Schofield, Brett R. (Frontiers in Neuroanatomy, 2014)
Perineuronal nets (PNs) are aggregates of extracellular matrix that have been associated with neuronal plasticity, critical periods, fast-spiking cells and protection from oxidative stress. Although PNs have been reported in the auditory system in several species, there is disagreement about the distribution of PNs within the inferior colliculus (IC), an important auditory hub in the midbrain. Furthermore, PNs in many brain areas are preferentially associated with GABAergic cells, but whether such an association exists in the IC has not been addressed. We used Wisteria floribunda agglutinin staining and immunohistochemistry in guinea pigs to examine PNs within the IC. PNs are present in all IC subdivisions and are densest in the central portions of the IC. Throughout the IC, PNs are preferentially associated with GABAergic cells. Not all GABAergic cells are surrounded by PNs, so the presence of PNs can be used to subdivide IC GABAergic cells into “netted” and “non-netted” categories. Finally, PNs in the IC, like those in other brain areas, display molecular heterogeneity that suggests a multitude of functions.